Effects of lactic acid bacteria isolated from Tibetan chickens on the growth performance and gut microbiota of broiler - Wang, Lei; Lin, Zhengrong; Ali, Mahboob; Zhu, Xiaohui; Zhang, Yu; Li, Siyuan; Li, Kun; Kebzhai, Fareeda; Li, Jiakui (Frontiers in Microbiology, 2023)
Lactic acid bacteria (LAB) are organic supplements that have several advantages for the health of the host. Tibetan chickens are an ancient species that has a unique gut microbial community due to its adaptation to the hypoxic environment of high altitude. However, knowledge of LAB isolated from Tibetan chickens is very limited. The purpose of this study was to assess the probiotic properties of Lactobacillus Plantarum (LP1), Weissella criteria (WT1) and Pediococcus pentosaceus (PT2) isolated from Tibetan chickens. To validate this, the broiler chicken growth experiment, serum biochemical test, real-time PCR, and 16s rDNA sequencing were conducted to study the probiotic effects of LP1, WT1, and PT2. Our findings showed that LP1, WT1 and PT2 were excellent inhibitors against Escherichia coli (E. coli ATCC25922), meanwhile, LP1, WT1 and PT2 significantly increased weekly weight gain, villus height, antioxidant ability and gut microbiota diversity indexs in broilers. In addition, LP1 and PT2 increased the relative abundance of Lactobacillus and decreased Desulfovibrio in comparison with T1 (control group). Additionally, oral LAB can reduce cholesterol and regulate the expression of tight junction genes in broiler chickens, suggesting that LAB can improve the integrity of the cecal barrier and immune response. Thus, it has been shown that LAB can improve growth performance, gut barrier health, intestinal flora balance and immune protection of broiler chickens. Our findings revealed the uniqueness of LAB isolated from Tibetan chickens and its potential as a probiotic additive.